KONSEP DAN TEORI PENDIDIKAN AGAMA ISLAM DI PONDOK PESANTREN AL BASHIROH WAL IBROH - Ahmad Nur Fadhilla; Sodiq Hidayatulloh; Fitra Tunnisa; Wida Tussyariah; Dela; Ami Latifah (UNISAN JURNAL, 2023)
The title of this research is the Al Bashiroh Ciganjur Islamic Boarding School learning model, South Jakarta. This research aims to:1) describe the analysis of learning needs at the Al Bashiroh Islamic boarding school. 2) know the learning design of Al Bashiroh Islamic boarding school 3) explain the efforts to implement learning at the Al Bashiroh Islamic boarding school. This type of research is descriptive qualitative with three approaches, namely sociological, phenomenological and psychological. This research uses interview and observation guidelines as data collection techniques. The data processing technique is carried out in 3 (stages), namely editing, coding and tabulating. In analyzing the data, researchers used qualitative descriptive analysis. Data regarding needs analysis and learning design and their implementation are analyzed using non-statistical data analysis techniques. The research results show that the learning process at the al Bashiroh Islamic boarding school, especially at Diniyah Madrasah, is going well. This can be seen in teachers who are able to use learning methodologies well, including varied learning methods and materials, learning materials are not focused on the text of students’ textbooks, creating a humorous atmosphere so that students are not too tense in their learning. Good learning makes students interested and happy in participating in the learning process in the classroom. The teachers’ efforts to grow and develop the existing learning process include continuing to try to vary methodologies in learning, cultivating active communication with students when explaining in class, explaining material that is easy for students to understand and providing motivation. The implication of this research is that it is hoped that the learning process carried out at the Al Bashiroh Islamic boarding school will need to maintain continuity in the use of more varied learning methodologies. Therefore, foundations and educational staff must provide adequate contributions. And teachers need to be more astute in developing learning methodologies so that the process runs more effectively and efficiently.